FORMATION OF CONVERSATIONAL SKILLS OF STUDENTS IN FOREIGN LANGUAGE CLASSES - Abdujabborova Malika Abduvaitovna (Journals Park Publishing, 2022)
The article scientifically substantiates the theoretical and methodological foundations of teaching using various methods and interactive methods, i.e. games, in the formation of students' speaking skills in the classroom in a foreign language. Currently, there are various pedagogical technologies that differ from each other in their focus and purpose. But the general aspect is that it helps to develop the thinking of students. We know that in recent years there has been an increased emphasis in education on student activation and development of thinking, but its practical application has been very slow. Dozens of theories and approaches are given in the pedagogical literature, based on such terms as improving education, optimizing the educational process, developing learning, active new (innovative) teaching methods, problem-based learning, programmed learning. A person strives to live with the traits and qualities instilled through education throughout his life.
Keywords: innovations, methods, tools, traditional methods, problem-based learning method, theory, approaches, programmed learning.